Faktor-faktor yang mempengaruhi perpindahan merek Asus ke merek lain - Tini Utami; suprihono setyawan; A. Suwondo (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study aims to examine "Analysis of the influence of dissatisfaction, product attributes, and the need for variation, on the switching of the Asus brand ". This data research used a questionnaire with a scale of 1-5 with a sample of 96 respondents. This sampling technique uses a non probability sampling with technique purposive sampling . The data obtained were then analyzed with the SPSS . The results of this study partially (1) Dissatisfaction has a positive and significant effect on brand switching based on the value of t count > t table that is 3.575 > 1.662 with a significant 0.001 < 0.05. (2) Product attributes have a positive and significant effect on brand switching based on the value of t count > t table, namely 2.362 > 1.662 with a significant 0.002 < 0.05. (3). The need to look for variations has a positive and significant effect on brand switching based on the t count > t table, namely 6.472 > 1.662 with a significant 0.000 <0.05. (4) Simultaneously, dissatisfaction, product attributes, and the need for variation have a positive and significant effect on brand switching. Based on the calculated F value < F table that is 111.918> 3.945 with a significant 0.000 <0.005. Based on Adjusted R Square that is equal to 0.778. In this case, it means that 77.8% of the variation in the brand switching variable is explained by the variables of dissatisfaction, product attributes, and the need to seek variation. Meanwhile, the remaining 22.2% is explained by other variables outside the model